Effects of prebiotics in combination with probiotics on intestinal hydrolase activity, microbial population and immunological biomarkers in SD rats fed an AIN-93G diet - Min-Jeong Kim; Dong-Gyeong Jeon; Yong Lim; Insurk Jang (Laboratory Animal Research, 2022)
Abstract Background Gastrointestinal microbiota, which comprises hundreds of different types of microbes, biologically plays crucial roles in the host’s health. Probiotics (PRO) did not always have a positive benefit on the host, depending on strains of microbes and the physiochemical properties of prebiotics (PRE), indicating that the properties of PRE in combination with PRO might have different effects on the gut ecology. The aim of this study was to assess the effects of insoluble or soluble PRE with PRO on intestinal digestive hydrolase, the fecal microbes, and immunological biomarkers in SD rats fed an AIN-93G diet. Results Forty, 8-week-old SD rats were randomly assigned to 4 groups with 10 replicates in each; cellulose (CELL), cellulose + probiotics (CELPRO), oatmeal (OATS), and oatmeal + probiotics (OATPRO) groups. After 4-week feeding trial, rats were treated with saline or lipopolysaccharide (LPS, 1 mg/kg) to examine the alleviating effects of PRO and PRE on immunological responses. There was a significant (p < 0.05) decrease in feed intake of rats fed the oatmeal supplemented diet without affecting growth performance. Blood triglyceride was significantly (p < 0.05) decreased in rats fed the oatmeal diet, and aspartate aminotransferase (AST) was significantly (p < 0.05) decreased in rats fed the PRO supplemented diet. Intestinal maltase, sucrose, and lactase activities were significantly (p < 0.05) higher in rats fed PRO compared with rats not fed PRO. Rats fed the oatmeal showed a significant (p < 0.01) increase in the fecal colony forming units (CFU) of Lactobacillus plantarum, Bacillus subtilis, and Saccharomyces cerevisiae compared with those fed cellulose. LPS-treated rats fed PRO showed a significant (p < 0.05) increase in blood secretory immunoglobulin A (sIgA) compared with those not fed PRO. The LPS-treated rats fed PRO resulted in decreased (p < 0.05) blood IL-6 compared with those not fed PRO, indicating that a dietary PRO alleviated inflammatory response in LPS-treated rats. Conclusions Dietary oatmeal increased fecal microbes, and PRO supplement resulted in increased intestinal hydrolase and immune functions of the host, demonstrating that soluble PRE with supplemented with PRO could be a more bioactive combination of synbiotics in SD rats.